Phage FR38 Treatment on Sprague Dawley Rat Inferred from Blood Parameters and Organ Systems - DEWI SARTIKA; SRI BUDIARTI; MIRNAWATI SUDARWANTO (Bogor Agricultural University, Indonesia, 2012)
The ability of phage FR38 to lysis indigenous Salmonella P38 from feces of diarrheal patient has been studied. However, effects of phage FR38 on organ system were not revealed as yet. This study was conducted to observe the effect of phage FR38 on blood chemistry, kidney functions, and liver functions. Twelve Sprague-Dawley rats were used as a model for this study that were divided into two groups; (i) control and (ii) treated group with phage FR38. For treated phage group, each rat was administered by 5 ml/kg bw of 1.59·107 pfu/ml of phage intragastric. The blood parameters were analysed on day 16. The results revealed that body and organs weight, erythrocyte, hematocrit, hemoglobin, leukocyte, total protein, creatinine, SGOT, and SGPT of phage treatment rats were not significantly different with the control rats on day 16 (P > 0.05). Therefore, this study showed was no effect of phage FR38 on body weight, blood chemistry, kidney and liver functions of the rat (P > 0.05).